KETERAMPILAN MEMBERIKAN PENGUATAN PEMBELAJARAN (MICRO TEACHING) - Ginting, Rahmadani Fitri; Mustika, Intan Sicha (Cahaya Ilmu Bangsa Institute, 2024)
The skill of providing learning reinforcement through the micro teaching method is a crucial aspect in the increasingly developing world of education. In the current era of globalization and information technology, demands for the quality of education are increasingly high, so teachers are required to have adequate skills in delivering learning material. This research aims to explore and analyze the skills of providing learning reinforcement in the context of micro teaching. By focusing on developing teacher competency, this research is expected to identify effective strategies and techniques used in providing positive reinforcement to students. This research method uses a qualitative approach with descriptive methods. The data in this research are in the form of words and actions carried out by teachers when providing reinforcement in learning. The research results showed that the skill of providing reinforcement in learning, especially in the context of micro teaching, is a crucial element that can influence the effectiveness of the teaching and learning process. Through appropriate verbal and nonverbal reinforcement, teachers are able to significantly increase student motivation and engagement. Additionally, the ability to provide immediate and specific feedback, as well as tailor reinforcement approaches based on individual student needs, is critical to creating a positive and inclusive learning environment